Hydrocyanic acid content in cassava tissues as a function of evaluation time and nitrogen fertilization - Oliveira, Natália Trajano de; Uchôa, Sandra Cátia Pereira; Alves, José Maria Arcanjo; Sediyama, Tocio; Albuquerque, José de Anchieta Alves de; Souza, Everton Diel; Melville, Cirano Cruz (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate hydrocyanic acid contents in cassava plants, according to the evaluation time and nitrogen fertilization. A randomized complete block design was used in a split‑plot arrangement, with four replicates. Nitrogen topdressing doses (0, 30, 60, 150, and 330 kg ha-1) were allocated in the plots, and the evaluation times (90, 120, 150, 180, 240, 300, and 360 days after planting), in the subplots. Hydrocyanic acid content was evaluated on leaf tissue, stalk, pulp, and root skins of the Aciolina cultivar. The effects of N doses and harvest times were independent. Nitrogen levels between 219 and 241 kg ha-1 provide the highest hydrocyanic acid contents, varying from 332 to 401 mg kg-1 of fresh matter in the evaluated tissues. Prolonging the evaluation time linearly reduces the hydrocyanic acid content in the tissues. Root skins accumulate the highest level of hydrocyanic acid, and the root pulp the lowest. At harvest, 360 days after planting, this cultivar is classified as sweet cassava.